Influential factors in the internationalization of African palm companies in the Quinindé canton, Esmeraldas - Ortega Paredes, Jomaira; Armas Aria, Mario (mktDESCUBRE; Vol 1 No 18 (2021): Eighteenth Edition (July - December), 2021)
The current article is a descriptive non-experimental investigation. The objective is to identify the factors that have influenced the internationalization of companies that are part of the palm growing sector located in Quinindé, a city in Esmeraldas province. To do this, in the research it was applied an intentional non-probabilistic sample of three companies that produce and commercialize African Palm. A semi-structured interview was applied with the dimensions raised in previous studies, through which the export capacity of the companies could be measured, and also analyzed and identified the factors that influence their process of internationalization. The results show that the productive factor with practices focused on quality and the technical certifications obtained such as fair trade, affect the internationalization processes of the studied organizations. After this research, it can be concluded that the productive, commercial and management factors have allowed the studied companies to commercialize their production in the international market.